The Transformative Role of Educators in Indian Higher Education and Societal Development - Mataboge, Collen (Journal of Educational Research and Policies, 2025)
Indian Higher Education has experienced phenomenal expansion since independence. The recent developments in communication and technology have removed all barriers of time and distance. A teacher plays a prominent role in bringing about social change and transmission of wisdom, knowledge and experience of one generation to the other. Children who are the potential wealth of the nation are under the influence of the teacher. The success of a nation depends on the quality of its people, which, in turn, depends on the younger generation. Teachers are the source of inspiration and guidance in the academic life of the students. In India, the position of the teacher in society was sacred from ancient times. In the Vedic and Post Vedic period, the place of the teacher was second to that of God. The teacher was acknowledged as the repository of all knowledge. Society believed in the teacher and his capacity to mould the younger generation. It admired his scholarship, dedication to duty and his intellectual and moral stature. His austere lifestyle and simple needs were considered as exemplary virtues to be imbibed by the younger generation. He occupied a very high position because he was not only the custodian of knowledge but also because he was a man of character and discipline. But today the status of the teacher is deteriorating. Teachers are not given much respect as it was given in ancient India.